Should They Stay or Should They Go? The Utility of C-Reactive Protein in Predicting Readmission and Anastomotic Leak After Colorectal Resection. Issue 2 (February 2019) - Pantel, Haddon J.; Jasak, Lisa J.; Ricciardi, Rocco; Marcello, Peter W.; Roberts, Patricia L.; Schoetz, David J.; Read, Thomas E.
Abstract : BACKGROUND: Hospital readmission and anastomotic leak following colorectal resection have a negative impact on patients, surgeons, and the health care system. Novel markers of patients unlikely to experience these complications are of value in avoiding readmission. OBJECTIVE: This study aimed to determine the predictive value of C-reactive protein for readmission and anastomotic leak within 30 days following colorectal resection. DESIGN: This is a retrospective review of a prospectively compiled single-institution database. PATIENTS: From January 1, 2013, to July 20, 2017, consecutive patients undergoing elective colorectal resection with anastomosis without the presence of proximal intestinal stoma, who had C-reactive protein measured on postoperative day 3, were included. MAIN OUTCOME MEASURES: The primary outcome measured was the predictive value of C-reactive protein measured on postoperative day 3 for readmission or anastomotic leak within 30 days after colorectal resection. RESULTS: Of the 752 patients examined, 73 (10%) were readmitted within 30 days of surgery and 17 (2%) had an anastomotic leak. Mean C-reactive protein in patients who neither had an anastomotic leak nor were readmitted (127 ± 77 mg/L) was lower than for patients who were readmitted (157 ± 96 mg/L, p = 0.002) and lower than for patients who had an anastomotic leak (228 ± 123 mg/L, p = 0.0000002). The area under the receiver operating characteristic curve for the diagnostic accuracy of C-reactive protein for readmission was 0.59, with a cutoff value of 145 mg/L, generating a 93% negative predictive value. The area under the curve for the diagnostic accuracy of C-reactive protein for anastomotic leak was 0.76, with a cutoff value of 147 mg/L generating a 99% negative predictive value. LIMITATIONS: This study was limited by its retrospective design and because all patients were treated at a single center. CONCLUSIONS: Patients with a C-reactive protein below 145 mg/L on postoperative day 3 after colorectal resection have a low likelihood of readmission within 30 days, and a very low likelihood of anastomotic leak. SeeVideo Abstract athttp://links.lww.com/DCR/A761 .